Secretagogin expression delineates functionally-specialized populations of striatal parvalbumin-containing interneurons - Garas, F; Shah, R; Kormann, E; Doig, N; Vinchiati, F; Nakamura, K; Dorst, M; Smith, Y; Magill, P; Sharott, A (eLife Sciences Publications, 2016)
Corticostriatal afferents can engage parvalbumin-expressing (PV+) interneurons to rapidly curtail the activity of striatal projection neurons (SPNs), thus shaping striatal output. Schemes of basal ganglia circuit dynamics generally consider striatal PV+ interneurons to be homogenous, despite considerable heterogeneity in both form and function. We demonstrate that the selective co-expression of another calcium-binding protein, secretagogin (Scgn), separates PV+ interneurons in rat and primate striatum into two topographically-, physiologically- and structurally-distinct cell populations. In rats, these two interneuron populations differed in their firing rates, patterns and relationships with cortical oscillations in vivo. Moreover, the axons of identified PV+/Scgn+ interneurons preferentially targeted the somata of SPNs of the so-called ‘direct pathway’, whereas PV+/Scgn- interneurons preferentially targeted ‘indirect pathway’ SPNs. These two populations of interneurons could therefore provide a substrate through which either of the striatal output pathways can be rapidly and selectively inhibited to subsequently mediate the expression of behavioral routines.